2023
DOI: 10.1039/d2fo01188c
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces DNA damage-mediated cancer cell senescence through the DLC1–DYRK1A–EGFR axis

Abstract: Inducing cell senescence is widely regarded as a potent tumor suppression mechanism. Resveratrol has attracted increasing attention for its capacity to prevent and suppress cancer. However, the mechanism of resveratrol...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The imbalance of ROS induces adverse cancer outcomes by affecting signal transduction within the DDR [ 93 ] because the accumulation of ROS can be toxic to cells, and toxic levels of ROS have been shown to affect replication and transcription by inducing DNA strand breaks and base oxidation, which may lead to the accumulation of mutations in organisms and the transformation of tumors [ 94 ]. It was found that due to the increased expression of the tumor-suppressant gene deleted in liver cancer 1 (DLC1), ROS could further inhibit the DYRK1A–EGFR axis, triggering DNA damage, while the DNA double-strand break marker protein γH2AX was up-regulated and the DNA repair-related proteins p-BRCA1 and RAD51 were down-regulated, which contributed to tumor inhibition [ 95 ]. Irreversible DNA damage is a key factor in tumor cell apoptosis.…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…The imbalance of ROS induces adverse cancer outcomes by affecting signal transduction within the DDR [ 93 ] because the accumulation of ROS can be toxic to cells, and toxic levels of ROS have been shown to affect replication and transcription by inducing DNA strand breaks and base oxidation, which may lead to the accumulation of mutations in organisms and the transformation of tumors [ 94 ]. It was found that due to the increased expression of the tumor-suppressant gene deleted in liver cancer 1 (DLC1), ROS could further inhibit the DYRK1A–EGFR axis, triggering DNA damage, while the DNA double-strand break marker protein γH2AX was up-regulated and the DNA repair-related proteins p-BRCA1 and RAD51 were down-regulated, which contributed to tumor inhibition [ 95 ]. Irreversible DNA damage is a key factor in tumor cell apoptosis.…”
Section: Ros Levels In Cancer Cells and Cancer Developmentmentioning
confidence: 99%
“…They become flattened and enlarged with large polypoid nuclei and lose their ability to divide [ 7 ]. These changes affect cytoskeleton integrity, cell proliferation, cell migration, and angiogenesis, leading to vascular dysfunction [ 30 , 31 ]. microRNA has been reported to be involved in regulating the pathological process of vascular disease progression, making it a potentially good candidate for stroke intervention.…”
Section: Discussionmentioning
confidence: 99%
“…46 induced DNA damage mediated cancer cell senescence by upregulating the γH2AX and downregulating the DNA repair proteins such as p‐BRCA (breast cancer gene 1) and RAD51 (RADiation sensitive protein 51 recombinase). Also, 46 effectively inhibited the volume of the transplanted tumors in a chicken embryo allantoic membrane xenograft tumor model (; Ma et al, 2023).…”
Section: Novel Drug Candidates Obtained From Natural Sources With Egf...mentioning
confidence: 99%